Epstein–Barr virus infection and nasopharyngeal carcinoma - Tsao, Sai Wah; Tsang, Chi Man; Lo, Kwok Wai (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2017)
Epstein–Barr virus (EBV) is associated with multiple types of human cancer, including lymphoid and epithelial cancers. The closest association with EBV infection is seen in undifferentiated nasopharyngeal carcinoma (NPC), which is endemic in the southern Chinese population. A strong association between NPC risk and the HLA locus at chromosome 6p has been identified, indicating a link between the presentation of EBV antigens to host immune cells and NPC risk. EBV infection in NPC is clonal in origin, strongly suggesting that NPC develops from the clonal expansion of a single EBV-infected cell. In epithelial cells, the default program of EBV infection is lytic replication. However, latent infection is the predominant mode of EBV infection in NPC. The establishment of latent EBV infection in pre-invasive nasopharyngeal epithelium is believed to be an early stage of NPC pathogenesis. Recent genomic study of NPC has identified multiple somatic mutations in the upstream negative regulators of NF-κB signalling. Dysregulated NF-κB signalling may contribute to the establishment of latent EBV infection in NPC. Stable EBV infection and the expression of latent EBV genes are postulated to drive the transformation of pre-invasive nasopharyngeal epithelial cells to cancer cells through multiple pathways. This article is part of the themed issue ‘Human oncogenic viruses’.